Maternal vitamin D status in relation to infant BMI growth trajectories up to 2 years of age in two prospective pregnancy cohorts - Anna Amberntsson; Linnea Bärebring; Anna Winkvist; Lauren Lissner; Helle Margrete Meltzer; Anne Lise Brantsæter; Eleni Papadopoulou; Hanna Augustin (Wiley, 2022)
Abstract Background Early childhood growth can affect the child's health status later in life. Maternal vitamin D status has been suggested to affect early childhood growth. However, there is a lack of studies investigating the role of maternal vitamin D status on growth trajectories during infancy. By using growth mixture modeling (GMM), maternal vitamin D status during pregnancy can be investigated in relation to different classes of infant growth trajectories. Objectives To examine the association between maternal 25‐hydroxyvitamin D (25OHD) and classes of infant body mass index (BMI) growth trajectories. Methods Mother-child pairs were included from the Norwegian Mother, Father, and Child Cohort Study (MoBa, n = 2522) and the Swedish GraviD cohort (n = 862). Maternal 25OHD in pregnancy was analyzed by liquid chromatography tandem mass spectrometry. Children's weights and heights were registry‐based. GMM identified classes of infant BMI growth trajectories up to 2 years. The association between maternal 25OHD and infant BMI class by cohort was estimated using a log‐link generalized linear model. Mixed model analysis estimated the pooled association including both cohorts. Results Two infant BMI classes were identified, stable normal and stable high. In MoBa, maternal 25OHD <50 and 50-75 nmol/L were associated (RR 2.70, 95% CI 1.26-5.77 and RR 2.56, 95% CI 1.20-5.47) with a higher risk of the infant stable high BMI class, compared with 25OHD >75 nmol/L. In GraviD, no association was found. In pooled analysis, maternal 25OHD ≤75 nmol/L was non‐significantly associated with a higher risk of the stable high BMI growth class. Conclusions Maternal 25OHD ≤75 nmol/L may be associated with a higher class of BMI growth trajectory during infancy.